Nd: Yag laser treatment for sub-hyaloid hemorrhage in childhood acute leukemia - Khadka, D; Sharma, AK; Shrestha, JK; Pant, B; Pant, S; Shrestha, A (Nepalese Journal of Ophthalmology, 2012)
Introduction: Sub-hyaloid haemorrhage is common in acute leukemia. Objective: To investigate the effects of Nd: YAG Laser hyaloidotomy in 11 eyes of 8 patients with pre-macular haemorrhage in acute childhood leukemia. Materials and methods: Premacular sub-hyaloid haemorrhage is one of the leading causes of visual disability in children with acute leukemia. Eleven eyes of 8 patients attending Kanti Children Hospital and BP Koirala Lions Centre for Ophthalmic Studies from January 2006 to July 2007 with premacular subhyaloid haemorrhage were included in the study and treated with Nd: YAG Laser. The haemorrhage originated from acute myeloid leukemia (AML) in 4 cases (6 eyes) and acute lymphoblastic leukemia (ALL) in 4 cases (5 eyes). Results: Drainage of premacular sub-hyaloid haemorrhage into the vitreous cavity within 3 months succeeded in 9 eyes out of 11 eyes treated. One eye had a dense clotted haemorrhage and the other had a re-bleed. Overall visual improvement was equal in both AML and ALL cases. No obvious epiretinal membrane, retinal breaks and tractional retinal detachment occurred in any eye. Conclusion: Nd: Yag laser hyaloidotomy is a relatively safe, simple and alternative treatment for eyes with a dense premacular sub-hyaloid haemorrhage in acute childhood leukemia. The risks and benefits have to be weighed in randomized clinical trials to establish Nd: YAG hyaloidotomy treatment as a routine procedure in leukemic children. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5860 NEPJOPH 2012; 4(1): 102-107